Child Abuse, Misdiagnosed by an Expertise Center: Part I-Medico-Social Aspects - Marianne Vlaming; Pieter J. J. Sauer; Emile P. F. Janssen; Peter J. van Koppen; Cornelis M. A. Bruijninckx; Marga W. M. Akkerman-Zaalberg van Zelst; H. A. Martino Neumann; Martin J. C. van Gemert (MDPI AG, 2023)
Child abuse is a dangerous situation for an infant. Professionals need to weigh the risk of failing to act when children are seriously harmed against the serious harm done by carrying out safeguarding interventions. In severe cases, foster care might be advisable. The negative effects for the child's psychosocial development requires that such placement must be based on very solid evidence. Our aim is to identify why Dutch parents whose child may have a medical condition that could mimic symptoms of child abuse have a significant chance of being erroneously convicted and losing custody of their child. As a method, we describe and analyze the following case. An Armenian-Dutch newborn (uncomplicated term vaginal delivery), starting at two weeks after birth, developed small bruises on varying body locations. At two months, a Well-Baby Clinic physician referred the girl to a university hospital, mentioning that there were no reasons to suspect child abuse and that her Armenian grandmother easily bruised as well. However, before consultation by a pediatrician of the hospital-located Expertise Center for Child Abuse, the parents were suspected of child abuse. Based on the expertise center's protocols, skeletal X-rays were made, which showed three healed, asymptomatic rib fractures, while invalid statistics suggested, incorrectly, a 10-100 times more likely non-accidental than accidental cause of the symptoms (discussed in Part II of this series). The expertise enter physician ignored any argument that could show parental innocence, including the positive parent-child relationship reported by the Well-Baby Clinic and the general practitioner. The girl and her older brother were placed in a family foster home and then in a secret home. The case radically resolved when a large bruise also developed there, and an independent tissue disease specialist diagnosed a hereditary connective tissue disorder in the mother, implying that the girl's bruises and rib fractures could well be disease-related. In conclusion, if child abuse is suspected, and foster care placement considered, the patient and the parents should be thoroughly investigated by an independent experienced pediatrician together with an experienced pediatric clinical psychologist or psychotherapist to produce an independent opinion. Children deserve this extra safeguard before being separated from their parents.